Analysis of LCMS-based untargeted metabolomics data 2 - Franceschi, Pietro (Henry Stewart Talks, 2018)
Peak picking in xcms, xcms – CentWave, Wavelet based filtering for chromatographic peaks, LC-MS metabolomics, Peak alignment, Warping: some general considerations, Missing values, Sample normalization, Annotation